Justification scheme for milling waffle background - E. V. Krivonos (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In the manufacture of dry and fuel compartments of missiles ensuring weight tolerance is a priority. In practice, this is ensured by the introduction of lightweight materials together with the optimal design of the supporting set of ribs (waffle background) of orthotropic shells and waffle shells. The manufacturing technology of which is difficult and costly in view of the difficulty of ensuring the accuracy and perfection of the shape of the waffle background cell. In modern conditions, when manufacturing a waffle shell for a fuel tank, reinforcement processing is carried out by milling on a monolithic blank using specialized machine systems. At the same time, the choice of the waffle background processing scheme remains an urgent issue: on a flat panel or on a bent shell. The problem of selection arises due to the requirements for the accuracy of the waffle background. It is important to maintain the part mass tolerance and geometric perfection of the cell shape. All this generally affects the perception of design loads and the carrying capacity of the rocket. At the same time, the methods and processes of processing the waffle background should be productive and economically feasible. The proposed justification will make it possible at the start of the design of new promising products to more accurately determine the technological and production costs necessary for the production of parts with a waffle background with given parameters and accuracy.